Mechanosynthesis of a Structurally Characterized, Well‐Defined Graphitic Phosphorus‐Linked Carbon Nitride (g‐PCN) with Water Splitting Activity. Issue 35 (26th October 2022) - Fiss, Blaine G.; Douglas, Georgia; Ferguson, Michael; Becerra, Jorge; Valdez, Jesus; Do, Trong‐On; Friščić, Tomislav; Moores, Audrey
Abstract: Graphitic phosphorus‐linked triazine networks (g‐PCNs) are an emergent class of carbon nitride materials that have attracted attention for their potential role in developing metal‐free water splitting photocatalysts, but remain difficult to access due to complicated synthetic procedures based on long reaction times, high‐temperature annealing (above 500 °C), and poor structural understanding. Here, a mild, lower temperature approach for the synthesis of catalytically active g‐PCN through combining a room‐temperature mechanochemical reaction of sodium phosphide and cyanuric chloride with only 1 h annealing at 300 °C is presented. Notably, this mechanosynthesized material is sufficiently ordered to permit unprecedented structural characterization of a g‐PCN layered solid by combining solid‐state magic angle spinning, nuclear magnetic resonance spectroscopy, X‐ray photoelectron spectroscopy, powder X‐ray diffraction (PXRD), and transmission electron microscopy, supported by dispersion‐corrected density functional theory modeling. The excellent match of experimental 31 P MAS NMR and PXRD data with modeling of the structure based on phosphorus‐linked triazine network layers makes the herein described mechanochemically synthesized material the first example of a photocatalytically active, as well as structurally characterized, g‐PCN. Abstract : The mild mechanochemical and aging synthesis of a structurally well‐defined phosphorus‐linked triazine‐based carbon nitride (g‐PCN) is confirmed through a combination of powder X‐ray diffraction, X‐ray photoelectron spectroscopy, 31P solid‐state magic angle spinning, nuclear magnetic resonance spectroscopy, and density functional theory calculations. Experimental and theoretical results are in excellent agreement, and the resulting g‐PCN material shows improved photocatalytic hydrogen evolution.